Pengaruh Kreativtas Guru, Lingkungan Sosial, Dan Motivasi Belajar Terhadap Prestasi Belajar Ekonomi Peserta Didik - yusdiana, Yusdiana; Azis, Muhammad; Herman, Herman (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2019)
The study aimed to identify the direct influence of teachers’ creativity, social environment, and learning motivation towards economic learning achievement of sudents. the study used survey method with quantitative approach. The population of the study was all students at SMAN 7 Soppeng in Soppeng district. Sample was selected by employing stratified sampling technique with sample proportional type. The instruments used to collect the data were quesytionnaire, observation, and documentation. The result of study reveal that there is no direct influence of teachers’ creativity on learning achievement and there is indirect influence positively and significantly of teachers’ creativity on learning achievement through learning motivation, there is direct influence positively and significantly of social environment on learning achievement and indirect influence positively and significantly of social environment on learning achievement through learning motivation, there is direct influence positively and significantly of teachers’ creativity and social environment on learning motivation both partially and simultaneously, and there is direct influence positively and significantly of learning motivation on learning achievement